APLIKASI IRIGASI TETES DALAM MENGEFISIENSI AIR UNTUK TANAMAN HORTIKULTURA PADA KELOMPOK TANI DI SEMANGGA JAYA KABUPATEN MERAUKE PROVINSI PAPUA SELATAN - Jamaludin, Jamaludin; Nurcholis, Nurcholis; Wahida, Wahida (Jurnal Abdi Insani, 2025)
Limited water sources in Semangga Jaya village result in superior horticultural commodities that cannot be optimised in the summer. Therefore, an innovation is needed in the form of drip irrigation to overcome the limited water conditions. The purpose of this activity is to design and build a drip irrigation network on agricultural land so that it can save and be efficient in using water during the dry season. The method used in this activity is to provide information to partners about drip irrigation, irrigation network design, irrigation network installation and the advantages of drip irrigation. Furthermore, training was conducted on the manufacture, installation and operation of drip irrigation in the field. The results of this service activity are in the form of a drip irrigation network design consisting of main pipes, divider pipes, lateral pipes, application tools and control systems. The construction of drip irrigation into three stages, namely coordination and survey of farmer groups, preparation of tools and materials, construction of drip irrigation networks. Socialisation activities were conducted to explain the water needs of horticultural crops, water conservation, and drip irrigation system technology. The practice of network operation begins with the introduction of the components of the main unit of the irrigation network, the introduction and practice of installing divider pipes/manifolds, installing application tools on divider pipes, and finally the operation of drip irrigation equipment. It can be concluded that the insemination of drip irrigation technology was enthusiastically welcomed by the farmers as evidenced by the activeness of farmers asking questions during socialisation and training, and farmers want to apply this technology to their fields.